The Influence Of Stress Management On The Stress Level Of Nurses In The Emergency Room At Rsu Manado Medical Center - Irma M. Yahya; Sri Wahyuni; Venice V Surapati (Jurnal EduHealth, 2023)
Stress is an unpleasant psychological condition that suppresses one's self and soul beyond the limits of one's ability. Stress management is the ability to use (human) resources effectively to overcome mental and emotional disturbances or disorders that arise due to responses (responses). Nurses as professionals in hospitals are very susceptible to work stress that causes physiological, psychological and behavioral disorders where stress itself is a form of physical, psychological and mental tension. The purpose of the study was to determine the effect of stress management on nurse stress levels in the emergency room at RSU Manado Medical Center. This research is a quantitative study is a quantitative study through the use of correlation research with a cross-sectional method involving a sample of 14 respondents and using the sampling technique with a total sampling . Collecting data by using a questionnaire and processing data using Mc Nemar test with value (a=0.05) . The study results show that there is an effect of stress management on nurse stress levels with p value = 0.025 and value of (α ≤ 0.05). The conclusion of this study is that the effect of stress management on nurses' stress levels in the emergency room at RSU Manado Medical Center. Suggestions from this research are expected to be used as input for nurses learning process activities about stress management to reduce nurse stress